2004
DOI: 10.1080/0020714049052349
|View full text |Cite
|
Sign up to set email alerts
|

An empirical test of Woody and Bowers’s dissociated-control theory of hypnosis

Abstract: Woody and Bowers's dissociated-control theory predicts impaired performance on tasks indexing frontally mediated supervisory attentional functions during hypnosis, especially for high susceptibles. This prediction is tested using Stroop task behavioral performance to measure aspects of anterior-mediated supervisory attentional function. All measures of anterior-mediated attentional functions significantly declined during hypnosis. Interactions be-tween susceptibility and hypnosis condition showed specific chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 17 publications
6
42
0
1
Order By: Relevance
“…Multiple experiments have found poorer selective attention, as measured by the Stroop color-naming task (Stroop, 1935), among HS individuals following a hypnotic induction (Gruzelier, Gray, Kaiser, & Barker, 1997;Jamieson & Sheehan, 2004;Kaiser, Barker, Haenschel, Baldeweg, & Gruzelier, 1997;Sheehan, Donovan, & Macleod, 1988). Similar e↵ects have been reported for letter fluency (Gruzelier & Warren, 1993;Kallio, Revonsuo, Hamalainen, Markela, & Gruzelier, 2001).…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…Multiple experiments have found poorer selective attention, as measured by the Stroop color-naming task (Stroop, 1935), among HS individuals following a hypnotic induction (Gruzelier, Gray, Kaiser, & Barker, 1997;Jamieson & Sheehan, 2004;Kaiser, Barker, Haenschel, Baldeweg, & Gruzelier, 1997;Sheehan, Donovan, & Macleod, 1988). Similar e↵ects have been reported for letter fluency (Gruzelier & Warren, 1993;Kallio, Revonsuo, Hamalainen, Markela, & Gruzelier, 2001).…”
Section: Introductionsupporting
confidence: 55%
“…Although we have emphasized the dissimilarities of the two HS subtypes, they exhibited uniformity in their increased utilization of an e↵ortless response strategy (Jamieson & Sheehan, 2004) following a hypnotic induction. This increase may tap into the hypothesized experiential response set, a cognitive set characterized by a willingness to allow experiences to occur with minimal e↵ort (Tellegen, 1981).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple well-powered behavioural studies have suggested that highly suggestible individuals exhibit impaired performance on cognitive tasks known to depend on prefrontal cortex, such as selective attention and working memory (Farvolden & Woody, 2004;Jamieson & Sheehan, 2004;Khodaverdi-Khani & Laurence, 2016;Terhune et al, 2011c). Some of these effects have been observed at baseline whereas others have been restricted to a hypnotic induction, thereby clouding interpretation.…”
Section: Neurocognitive Bases Of Hypnosis and Hypnotic Suggestibilitymentioning
confidence: 97%